What Explains Uneven Female Labor Force Participation Levels and Trends in Developing Countries? - Klasen, Stephan (Published by Oxford University Press on behalf of the World Bank, 2021)
Rapid fertility decline, a strong expansion of female education, and favorable economic conditions should have promoted female labor force participation in developing countries. Yet trends in female labor force participation rates (FLFP) have been quite heterogeneous, rising strongly in Latin America and stagnating in many other regions, while improvements were modest in the Middle East and female participation even fell in South Asia. These trends are inconsistent with secular theories such as the feminization U hypothesis but point to an interplay of initial conditions, economic structure, structural change, and persistent gender norms and values. We find that differences in levels are heavily affected by historical differences in economic structure that circumscribe women's economic opportunities still today. Shocks can bring about drastic changes, with the experience of socialism being the most important shock to women's labor force participation. Trends are heavily affected by how much women's labor force participation depends on their household's economic conditions, how jobs deemed appropriate for more educated women are growing relative to the supply of more educated women, whether growth strategies are promoting female employment, and to what extent women are able to break down occupational barriers within the sectors where women predominantly work.